ASSOCIATION OF Cladosporium cladosporioides BROWN LEAF SPOT OF LADY PALM IN PAKISTAN - M. Ashfaq; M.a. Anjum; M. S. Haider; M. Ali; U. Mubashar; U. Bashir1 H.M.U Aslam; M. Sajjad (Journal of Animal and Plant Sciences, 2020)
Ladies palm (Rhapis excelsa L.) also known as broad leaf Lady palm is unique looking palm because of its appearance and beauty and, therefore, is commonly used for landscape purposes. Various fungal diseases are the major threat to Lady’s palm that affects its growth and beauty. In the year 2016, diseased leaf samples were collected from different locations i.e. Pattoki, Chunian, Kot Radha Kishan, Nathoki and Grinkot of district Kasur, Punjab, Pakistan to identify the pathogen. Based on various morphological characteristics, the casual organisms Cladosporium cladosporioides were isolated, purified and identified with FCBP 1562 from collected samples. The identified pathogen was further confirmed by using molecular analysis. For this purpose, Internal Transcribed Spacer (ITS) primer pairs were used i.e. ITS1 by using universal primer pair ITS1 reverse primer (3 ́- TCCTCCGCTTATTGATATGC-5 ́) and ITS1 forward primer (5 ́- TCCGTAGGTGAACCTGCGG-3 ́) for identification of casual organism from total genomic DNA of the isolated causal fungus. The pathogen was re-isolated and reconfirmed morphologically as Cladosporium cladosporioides from the artificially inoculated ladies palm plant leaves according to the Koch’s postulates. To our knowledge Cladosporium cladosporioides was reported first time in Pakistan and causes chlorosis and necrosis of the lady’s palm. The current study will be equally beneficial both for scientists and growers for controlling and management of this disease.
Keywords: Ladies palm; Cladosporium cladosporioides; brown spot; disease; Pakistan